Association of Mini Nutritional Assessment with anthropometric measurements and muscle strength in elderly people: a neglected risk group - Turker, Perim; Hoca, Mustafa (Progress in Nutrition, 2021)
Summary. Aim: Elderly individuals that are one of the neglected risk group are at a higher risk for health problems owing to inadequate and unbalanced nutrition. Nutritional status is also an important determinant of health in people over 65 years of age. Screening and diagnostic instruments are important in the recognition of the elderly people in evaluating the results of malnutrition. Unfortunately, there is no gold standard for the detection of malnutrition in elderly people. In this study, we aimed to assess the association of Mini Nutritional Assessment with anthropometric measurements and muscle strength in elderly people. Materials and Methods: A cross-sectional study included 210 elderly volunteers. Anthropometric measurements were taken, body mass index (BMI) values were calculated and muscle strength was evaluated by a hand dynamometer. Nutritional status was assessed using the Mini Nutritional Assessment (MNA) screening tool. The study was approved by Research Ethics Committee. Results: Elderly individuals with a BMI value of ≥ 30 kg/m2 had significantly lower right and left hand grip strengths than BMI values of 18.5-24.9 kg/m2 and 25-29.9 kg/m2. However, elderly individuals with a BMI of ≥ 30 kg/m2 had significantly higher waist/hip ratio, waist/height ratio, body fat percentage, waist, hip, calf, neck and mid-upper arm circumferences than BMI values of 18.5-24.9 kg/m2 and 25-29.9 kg/m2. Additionally, a positive and statistically significant correlation was determined between the right and left hand grip strengths and the MNA score in women. Conclusion: To improve the nutritional status, elderly people should be monitored at regular intervals by obtaining anthropometric and muscle strength measurements and performing nutritional status screening tests.